Efek Terapi Birth Ball pada Ibu Bersalin terhadap Intensitas Nyeri Persalinan Kala I Fase Aktif - Ika Murtiyarini; Rosmaria Rosmaria; Yuli Suryanti; Ry Eni Mian Marisi; Netti Herawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the effect of birth ball therapy on mothers giving birth to the pain intensity of the first active phase of labor. The method used was quasi-experimental with a one-group pretest-posttest design involving 40 mothers during the first active phase at PMB Nuriman Rafida, Jambi City, who were selected by accidental sampling. Research data were analyzed using paired t-tests. The results showed that most of the pain intensity of the mother before the study was carried out was in a severe category. After the intervention using a birth ball, the majority of the pain intensity of the mother in labor was in the moderate category (p-value = 0.000). In conclusion, there is an effect of birth ball therapy on reducing the intensity of labor pain during the first active phase. Keywords: Birth Ball, Active Phase, Labor Mother, Pain Intensity, First Stage of Labor